Analisis Pengaruh Good Corporate Governance Dan Ukuran Komite Audit Terhadap Thin Capitalization Perusahaan Perusahaan Pemilik Modal Asing - Elok Faiqoh Himmah (LPPM UNIBI, 2020)
This study aims to analyze the thin capitalization implemented in companies that have foreign capital. Thin capitalization is a financing structure from internal and external companies. This study uses the independent variable Good Corporate Governance and Committee Size. The population of this study consists of all non-financial companies listed on the Indonesia Stock Exchange from 2017-2019. This study took samples from companies that own foreign capital which are non-financial institutions. This study uses multiple linear regression analysis as a statistical method. The results of this study indicate that the size of the Audit Committee has a significant effect on thin capitalization